Competitiveness and wellbeing of Central Eastern European economies in the last decade - Małgorzata Runiewicz-Wardyn (Transformation, Integration and Globalization Economic Research (TIGER), 2018)
The goal of the current research is to review the competitiveness position of the Central Eastern European (CEE) countries of the EU in the last decade on the national (macro-), sectoral/industry (mezzo-) and companies (micro-) levels. For the purpose of the study the concept of international competitiveness was defined as the country's ability to grow and compete with other countries, shaped by the level of its productivity and the increase of value-added, so as hightech and highly innovative services sectors. Furthermore, the paper attempts to explore how competitiveness and wellbeing interlink: to which degree the improving competitiveness contributes to the overall levels of wellbeing in these countries. Finally, the paper draws a number of conclusions and suggestions for the further policy debate.
Keywords: 330; Internationaler Wettbewerb; Sozialer Indikator; Osteuropa